Biocide Effect of Non-Thermal Atmospheric Pressure Plasma - Daria I. Petrukhina; Irina V. Polyakova; Sergei A. Gorbatov (Техника и технология пищевых производств)
Introduction. New methods of sterilization with non-thermal atmospheric pressure plasma remain an extremely relevant field of food science. The present research estimated the effect of non-thermal argon plasma on lactic acid bacteria obtained from walnuts. Study objects and method. The non-thermal argon plasma was generated by electrode discharge induced by a coaxial microwave plasmatron at atmospheric pressure. The discharge was generated in a special electrode construction. Its stability was achieved via low gas flow through the discharge gap. Argon consumption was 10 L/min. The study involved Lactobacillus plantarum and Lactobacillus mali in their natural association and vegetative form. Endo’s medium (Endo agar) was inoculated with lactobacilli. 100 μl of the suspension were added into a Petri dish with nutrient medium and carefully rubbed with a spreader. The plates with Endo agar inoculated with lactobacilli were placed under plasma radiation at a distance of 45 mm. The biocidal effect of plasma radiation was estimated by the diameter of the affected areas. After the plasma treatment, the Petri dishes were incubated in an incubator for 24–48 h at 37°C, after which the diameters of the affected areas were measured again. Results and discussion. The paper introduces experimental data on the effect of argon plasma on lactobacilli isolated from food. After treating the surface of inoculated Petri dishes with non-thermal plasma for five minutes, the diameter of the inhibition zone reached the diameter of a Petri dish (80 mm) and exceeded the diameter of the spark gap of the plasma generator (36 mm). The temperature on the surface of the nutrient medium during plasma treatment was within the optimal temperature for lactobacillus growth, i.e. 37.3 ± 0.6°C, which excluded thermal effects. Only a few colonies survived a five-minute treatment. After one-minute treatment, the number of survived colony-forming units was considerably higher. Conclusion. Non-thermal argon plasma treatment proved effective in inhibiting the growth of gram-positive bacteria (Lactobacillus isolated from walnuts) on solid surfaces (agar plates). After five minutes of plasma treatment, the inactivated area (80 mm) exceeded the anode electrode cross section (36 mm) of the plasma generator.